KAJIAN SENSUALITAS PRIA PADA IKLAN MIRAEL SUGAR WAX VERSI JEFRI NICHOL DENGAN TEORI KRITIK SENI FELDMAN: A STUDY OF MALE SENSUALITY IN JEFRI NICHOL'S MIRAEL SUGAR WAX ADVERTISEMENT WITH FELDMAN'S ART CRITICISM THEORY - Monica Revias Purwa Kusuma (Universitas Trisakti, 2025)
A Study of Male Sensuality in Jefri Nichol's Mirael Sugar Wax Advertisement with Feldman's Art Criticism Theory. This study aims to examine the representation of male sexuality in the short video advertisement of Mirael Sugarwax featuring Jefri Nichol, uploaded on Instagram in February 2025. The advertisement showcases Jefri Nichol as a brand ambassador, a unique approach considering sugar wax is typically associated with women’s body care. Employing a qualitative descriptive method, this research applies Edmund Feldman’s art criticism framework, which includes stages of description, formal analysis, interpretation, and evaluation, complemented by Roland Barthes’ semiotics theory to analyze denotation, connotation, and myth. Data were collected through documentation and literature studies, with content analysis as the primary method. The findings reveal that the advertisement effectively constructs male sexuality through Jefri Nichol’s physical aesthetics, expressions of pleasure, and confidence across 15 scenes, such as undressing and facial expressions during waxing. However, excessive sensuality, such as the scene of smearing sugar wax on the mouth, has sparked negative reactions from netizens for being irrelevant and overly provocative. This study concludes that this advertisement is effective in promoting the product and can convey the message it wants to convey to the audience, the overemphasis on sensuality may detract from its professional image and lead to negative perceptions. This research provides insights into how male sexuality is portrayed in modern visual culture through advertising.